Kemampuan Daya Dukung Lingkungan Wisata Tirta Nirwana Songgoriti - Herlambang, Moch. Faisal; Wicaksono, Agus Dwi; Hidayat, AR Rohman Taufiq (Fakultas Teknik, Universitas Brawijaya, 2016)
Tirta Nirwana Songgoriti Tourism is one of main tourism destination in Batu City East Java. Currently, a fairly rapid growth can be seen from the quantity of tourist visit in the Tirta Nirwana Songgoriti Tourism which tends up from year to year. However, the embodiment of balance beetwen activity in tourist sites with environmental sustainability to be concern given the number of visitors who traveled quite high. The purpose of this research is to know the ability of Tirta Nirwana Songgoriti Tourism to accommodate the number of tourists during a visit to the unit of visits per day. The methods used in this research is using Cifuentes were modified to the Physical Carrying Capacity (PCC), Real Carrying Capacity (RCC), Management Capacity (MC), and Effective Carrying Capacity (ECC). The result of the calculation about carrying capacity conclude that the average number of tourists which can accommodate Tirta Nirwana Songgoriti Tourism is 148 tourists visit per day. The value wasn’t exceeded by the average tourist visits in the last 5 years which reached 131 tourist visitors per day. Keywords: Carrying Capacity, Tirta Nirwana Songgoriti, Tourist Visits